A study on self compacting concrete made with local material / Ahmad Rasidi Osman, Mohd Syahrul Hisyam Mohd Sani and Wan Zukri Wan Abdullah - Osman, Ahmad Rasidi; Mohd Sani, Mohd Syahrul Hisyam; Wan Abdullah, Wan Zukri (2004)
Recent remarkable changes in the construction environment are demanding improved technology for the production of high performance concrete with far greater workability, high strength and long durability. Therefore, a self-compacting concrete (SCC), which has excellent deformability and resistance to segregation and can be filled in heavily reinforced formwork without vibrators, was created. In order to verify the differences of the properties of hardened self-compacting concrete and normal vibrated concrete, various investigations have been carried out for establishing a rational mix-design and self-compactability testing method to make it a standard concrete. To achieve the performance goal, there are so many factors that have to be considered. It started from the application of local materials including the additive or admixture to enhance the flowability of concrete. It is followed by the concrete mix of varying design strength by using ordinary Portland cement (OPC) cement, aggregates of varying sizes, superplasticizers and fly ash which is expected to be effectively used for self-compacting concrete. The objective of this study is to find the local material that can be used as an admixture for self-compacting concrete (SCC). Local material that has been selected as an admixture is rubberwood ash. Ten different concrete mix designs are used as a mixture for sample of cube, cylinder and beam. Method that has been used to determine the self-compacting concrete (SCC) are V box! V- flow test and slump flow test. Standard testing methods to determine the strength of concrete are cube test for compressive strength, cylinder splitting test for tensile strength and flexural beam test for flexural strength. Through U flow test and slump flow test, it was found that concrete mix with rubberwood ash as an admixture failed to be classified as a self-compacting concrete (SCC). It was also found that concrete mix with rubberwood ash will decrease in compressive strength, tensile strength and flexural strength. Strength of concrete decrease with the increasing of amount rubberwood ash added.